HKROC: an integrated front-end ASIC to readout photomultiplier tubes for the Hyper-Kamiokande experiment. (1st January 2023) - Conforti Di Lorenzo, S.; Afiri, A.; Bolognesi, S.; Bombardi, G.; Bouyjou, F.; Callier, S.; De La Taille, C.; Dinaucourt, P.; Drapier, O.; Dulucq, F.; El Berni, A.; Extier, S.; et al.
Abstract: The HKROC ASIC was originally designed to readout the photomultiplier tubes (PMTs) for the Hyper-Kamiokande (HK) experiment. HKROC is a very innovative ASIC capable of readout a large number of channels satisfying stringent requirements in terms of noise, speed and dynamic range. Each HKROC channel features a low-noise preamplifier and shapers, a 10-bit successive approximation Analog-to-Digital Converter (SAR-ADC) (designed by AGH Krakow) for the charge measurement (up to 2500 pC) and a Time-to-Digital Converter (TDC) (designed by CEA IRFU group) for the Time-of-Arrival (ToA) measurement with 25 ps binning. HKROC is auto-triggered and includes all necessary ancillary services as bandgap circuit, PLL (Phase-locked loop) and threshold DACs (Digital to Analog Converters). This paper will describe the ASIC architecture and the experimental results of the first HKROC prototype received in January 2022.